2012
DOI: 10.1007/s10834-012-9309-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Credit Card Adoption in Urban China

Abstract: Analysis of data from the 2008 Survey of Chinese Consumer Finance and Investor Education indicated that 30.0 % of the sample households held at least one credit card. Significant factors associated with the probability that an urban Chinese individual would hold a credit card included income, age, education, occupation, and awareness of credit card risks, default consequences, the credit system, and that late payments increase interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…In the study from Singapore, credit cards can provide lower income households a line of credit that is easier to access than other potential sources of credit (Sharpe et al, 2012). However, several studies from different countries suggest that card ownership is positively related to income (Themba & Tumedi, 2012;Abdul-Muhmin & Umar, 2007;Kaynak & Harcar, 2001;Chan, 1997;Heck, 1987;Adcock et al, 1977).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the study from Singapore, credit cards can provide lower income households a line of credit that is easier to access than other potential sources of credit (Sharpe et al, 2012). However, several studies from different countries suggest that card ownership is positively related to income (Themba & Tumedi, 2012;Abdul-Muhmin & Umar, 2007;Kaynak & Harcar, 2001;Chan, 1997;Heck, 1987;Adcock et al, 1977).…”
Section: Resultsmentioning
confidence: 99%
“…The findings are consistent with the results from Botswana (Themba & Tumedi, 2012), Singapore (Ramayah et al, 2002) and USA (Hamilton & Khan, 2001). Sharpe et al (2012), in a study conducted in China, explained further that older cardholders had less awareness of the consequences of defaulting on payments. In contrast, a study from India (Khare et al, 2012) showed that younger cardholders were the ones who had the tendency to revolve while the findings from Saudi Arabia (Abdul-Muhmin & Umar, 2007) showed that age was not an influential variable when it came to determining the tendency to revolve.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations